TAMI-18. SINGLE-CELL SEQUENCING AND GENETIC LABELING TO CHARACTERIZE HYPOXIC GBM CELLS IN THEIR MICROENVIRONMENT. (9th November 2020) - Sattiraju, Anirudh; Marallano, Valerie; Ramakrishnan, Aarthi; Brusco, Concetta; Shen, Li; Wojcinski, Alexandre; Kesari, Santosh; Friedel, Roland H; Zou, Hongyan
Abstract: Glioblastoma (GBM) recurrence, arising from treatment-resistant hypoxic cells, is a major contributor to patient mortality. We have engineered GBM cell lines with a novel genetic reporter system ("HRE-UnaG"), which sensitively labels hypoxic cells with green fluorescence. Using murine GL261 HRE-UnaG GBM cells in intracranial transplants in immunocompetent hosts, we detected hypoxic cells primarily around pseudopalisading structures. Here, we report our new results of single cell RNA-seq sequencing of intracranial GL261-HRE-dUnaG GBM tumors, which revealed in hypoxic UnaG+ GBM cells upregulation of more than 60 genes, including canonical hypoxia response genes such as Slc2a1, Bnip3, Ldha and Vegfa, and downregulation of a smaller number of genes, such as Rgcc, Cdc20 and Hist1h2ap, which regulate cell cycle progression. This novel GBM hypoxia signature was in TCGA patient samples mostly upregulated in recurrent GBM and associated with worse prognosis, especially within proneural and mesenchymal subtypes. Gene set enrichment analysis revealed that the GBM hypoxia signature was positively correlated with hypoxia, glycolysis, TNFα and MTORC1 signaling, and negatively correlated with oxidative phosphorylation, Myc and DNA repair pathways. Subclustering revealed four distinct subpopulations of hypoxic GBM cells, which were distinguished by differential expression of pathway genes for proliferation, angiogenesis, stress response, and type I/II interferon signaling. Intercellular communication between hypoxic GBM cells and the stromal cells were predicted using NicheNET package. To spatio-temporally label in future studies hypoxic GBM cells and their progeny, we have engineered GBM cells with an inducible, hypoxia-sensitive lineage-tracing reporter (HRE-Cre; floxed-tdTomato). In combination with the HRE-UnaG hypoxia reporter, we will be able to reveal the role of "hypoxia memory" in GBM expansion and recurrence after treatment. Identifying key markers of hypoxic cells in respect to treatment resistance and relapse will lead to improvements in GBM detection and new options for therapeutic treatments.